Diet quality impairs male and female reproductive performance and affects the opportunity for selection in an insect model. Issue 11 (22nd November 2022) - Winkler, Lennart; Janicke, Tim
Abstract: Environmental factors can have profound effects on the strength and direction of selection and recent studies suggest that such environment‐dependent selection can be sex‐specific. Sexual selection theory predicts that male fitness is more condition dependent compared to female fitness, suggesting that male fitness is more sensitive to environmental stress. However, our knowledge about the effect of environmental factors on sex‐specific reproductive performance and on sex differences in the opportunity for selection is still very limited. In the present study, we investigated the sex‐specific effects of diet quality (yeast deprivation and flour type) in the red flour beetle Tribolium castaneum . Specifically, we manipulated yeast supplementation in wheat and whole‐wheat flour in competition assays allowing us to test for sex‐specific effects of food quality (i) on reproductive success and (ii) on the opportunity for selection. Our data show that yeast deprivation in wheat flour had significantly negative effects on body mass and reproductive success of both sexes, while high‐quality flour (whole‐wheat flour) was able to buffer the negative impact to a large extent. Importantly, our data suggest no sex‐specific effect of dietary stress on reproductive success because the magnitude of the negative effect of yeast deprivation was similar for males and females. Moreover, our study demonstrates that low food quality inflated the opportunity for selection and did not differ between sexes neither under benign nor stressful dietary conditions. We discuss the implications of our findings for the adaptation to stressful environments. Abstract : Environmental factors can have profound effects on the strength and direction of selection and recent studies suggest that such environmentdependent selection can be sex‐specific. We manipulated diet quality in an insect model finding no sex‐specific effect of dietary stress on reproductive success. Moreover, our study demonstrates that low food quality inflated the opportunity for selection and did not differ between sexes neither under benign nor stressful dietary conditions.